Let's solve the given problem step by step.
Part A:
-
Finding the GCF: The coefficients of the quadratic equation \(2x^2 + 22x + 60\) are:
- \(2\) (coefficient of \(x^2\))
- \(22\) (coefficient of \(x\))
- \(60\) (constant term)
The GCF of \(2\), \(22\), and \(60\) is \(2\).
-
Factoring out the GCF: If we factor out \(2\), we get: \[ 2(x^2 + 11x + 30) \]
-
Values for A, B, and C: The factored form yields the new coefficients:
- \(A = 1\) (from \(x^2\))
- \(B = 11\) (from \(11x\))
- \(C = 30\) (the constant term)
So for Part A, we have:
- The GCF is = 2
- The quadratic with the factored out the GCF is = 2(x^2 + 11x + 30)
- A = 1
- B = 11
- C = 30
Part B: Using the quadratic formula: \[ x = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \]
Plugging in the values we found:
- A = 1
- B = 11
- C = 30
So, we can fill in: \[ x = \frac{-11 \pm \sqrt{11^2 - 4(1)(30)}}{2(1)} \]
Part C: Now, let's calculate the discriminant and solve for \(x\):
-
Calculate \(B^2 - 4AC\): \[ B^2 - 4AC = 11^2 - 4 \cdot 1 \cdot 30 = 121 - 120 = 1 \]
-
Now, plugging this into our formula: \[ x = \frac{-11 \pm \sqrt{1}}{2} \] \[ x = \frac{-11 \pm 1}{2} \]
-
Calculating the two possible values for \(x\):
- For the lesser number: \[ x = \frac{-11 - 1}{2} = \frac{-12}{2} = -6 \]
- For the greater number: \[ x = \frac{-11 + 1}{2} = \frac{-10}{2} = -5 \]
So, we have:
- x = -6 (lesser number)
- x = -5 (greater number)
In summary, the filled blanks are:
-
The GCF is = 2
-
The quadratic with the factored out the GCF is = 2(x^2 + 11x + 30)
-
A = 1
-
B = 11
-
C = 30
-
x = -11 + sqrt{1} / 2
-
x = -6 (lesser number)
-
x = -5 (greater number)